High-performance concrete shield segment and preparation process thereof
By combining the modified biomass carbonization and adsorbing calcium lignosulfonate with traditional concrete materials, the problem of poor permeability of shield tube sheets is solved, and the effect of high strength and long-term durability is achieved.
Patent Information
- Application Number
- CN202411922628.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-25
AI Technical Summary
In the prior art, the concrete shield pipe sheet has poor permeability and is difficult to meet the needs of high strength and long-term durability.
By carbonizing biomass and adsorbing calcium lignosulfonate, modifying biomass carbon is formed, and a high-performance anti-seepage concrete shield tube sheet is prepared by combining cement, gravel, sand, fly ash, steel fibers and water reducing agents.
It improves the permeability and strength of concrete shield pipe sheets, extends its service life, and reduces permeability and shrinkage.
Smart Images

Figure CN119874263A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to a high-performance concrete shield segment and a preparation process thereof. Background Art
[0002] The shield segment is the main assembly component in shield construction and the innermost barrier of the tunnel. It is responsible for resisting soil pressure, groundwater pressure and some special loads. The shield segment is usually made of high-strength anti-seepage concrete. During the shield construction process, the shield machine relies on jacks to push the segment forward. At the same time, the segment plays a supporting role. After the installation is completed, a formed tunnel is formed. The design and construction of the shield segment is one of the key links in tunnel construction. The quality of its structural design is directly related to the stability, safety and service life of the tunnel.
[0003] Concrete shield segment structures have requirements for impermeability grade and sub-item durability. In order to meet the requirements of relevant indicators, the existing technology mainly improves the relevant performance by optimizing the formula, adding additives such as fiber and mineral admixtures, or improving the vibration curing process. Patent CN114988813A discloses an impermeable concrete for shield segments and a preparation method thereof, which includes, by weight: 430-450 parts of silicate cement, 50-58 parts of fly ash, 540-560 parts of sand, 1140-1160 parts of crushed stone, 120-140 parts of water, 100-110 parts of impregnated structural basalt fibers, and 20-23 parts of water reducers. The impregnation of structural basalt fibers improves the impermeability and strength of concrete. However, the impermeability of this method is poor and needs to be further improved.
[0004] Therefore, it is necessary to provide an improved high performance concrete shield segment and a preparation process thereof to solve the above problems. Summary of the invention
[0005] The purpose of the present invention is to provide a high-performance concrete shield segment and a preparation process thereof, by carbonizing biomass to adsorb calcium lignosulfonate, and utilizing the slow release of silicon dioxide and calcium lignosulfonate after carbonization of biomass to synergistically improve long-term high impermeability and strength.
[0006] To achieve the above-mentioned purpose, the present invention provides a high-performance concrete shield segment, comprising impermeable concrete and a steel cage, wherein the impermeable concrete comprises, by mass, 280-330 parts of cement, 500-570 parts of crushed stone, 400-480 parts of sand, 30-45 parts of fly ash, 20-35 parts of steel fiber, 5-18 parts of modified biomass carbon, 5-8 parts of water reducer, and 70-90 parts of water; the modified biomass carbon is obtained by carbonizing biomass with a crude fiber content of ≥30% and then adsorbing calcium wood sulfonate.
[0007] Furthermore, the preparation method of the modified biomass carbon includes: carbonizing the biomass at 500-700°C, then crushing and sieving; then adding it to an aqueous solution of calcium lignosulfonate, then freeze-drying, and then crushing and sieving to obtain the modified biomass carbon.
[0008] Furthermore, the mass fraction of calcium lignosulfonate in the calcium lignosulfonate aqueous solution is 5-12%, and the mass ratio of the carbonized biomass to calcium lignosulfonate is (5-10):1.
[0009] Furthermore, the carbonization treatment time is 1-3 hours; the crushing and screening refers to passing through a 100-200 mesh sieve.
[0010] Furthermore, the biomass includes one or more of straw, rice husk, hemp stalk, wood chips, bark, bamboo chips and bamboo powder, branches, coconut shells, walnut shells, palm shells, peanut shells, and coffee grounds.
[0011] Furthermore, the preparation method of the modified biomass carbon also includes: mixing the freeze-dried product with a silane coupling agent, and then drying, crushing and sieving to obtain the modified biomass carbon.
[0012] Furthermore, the fineness modulus of the sand is 2.3-3.3, and the crushed stone is 5-25 mm grade crushed stone.
[0013] The present invention also provides a process for preparing the high performance concrete shield segment as described in any one of the above, comprising the following steps:
[0014] S1. Concrete preparation: preparing concrete according to the raw material ratio of the impermeable concrete;
[0015] S2. Fabrication and installation of steel cage: prepare the segment mold, apply the release agent, process the segment steel cage, and hoist it into the mold for positioning and installation;
[0016] S4, concrete pouring and vibrating: pouring the concrete obtained in step S1 into a mold, vibrating, and forming a casting body;
[0017] S5, curing and demoulding: curing the cast body to obtain shield segments.
[0018] Furthermore, the curing refers to first steam curing or natural curing until the compressive strength of the concrete reaches 20MPa, and then hoisting it to a water curing tank for curing for 7-28 days.
[0019] The above technical solution conceived by the present invention has the following beneficial effects compared with the prior art:
[0020] 1. The present invention forms a porous structure by carbonizing biomass and then adsorbing calcium wood sulfonate, which can play a role in reducing water and preventing seepage. The selected high-fiber content biomass can also release silicon dioxide after carbonization, further improving the anti-seepage performance and strength. Moreover, the biomass charcoal itself can also improve the strength and hardness of concrete, and at the same time can also reduce the shrinkage rate and permeability of concrete.
[0021] 2. Increase the adsorption capacity of calcium wood sulfonate and the specific surface area of modified biomass carbon through freeze drying, thereby improving the mixing effect with cement and other powders and improving the impermeability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The present invention is a process flow chart for preparing high performance concrete shield segments. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0024] The invention provides a high-performance concrete shield segment, comprising impermeable concrete and a steel cage. The impermeable concrete comprises, by mass, 280-330 parts of cement, 500-570 parts of crushed stone, 400-480 parts of sand, 30-45 parts of fly ash, 20-35 parts of steel fiber, 5-18 parts of modified biomass carbon, 5-8 parts of water reducer, and 70-90 parts of water; the modified biomass carbon is obtained by carbonizing biomass with a crude fiber content of ≥30% and then adsorbing calcium wood sulfonate.
[0025] The biomass with high fiber content is selected, as its carbonized residue and porosity are high, which is conducive to the adsorption of calcium wood sulfonate and plays a long-term anti-seepage role through slow release; and the biomass charcoal itself can also improve the strength and hardness of concrete, while also reducing the shrinkage rate and permeability of concrete.
[0026] Furthermore, the preparation method of the modified biomass carbon includes: carbonizing the biomass at 500-700°C, then crushing and sieving; then adding it to an aqueous solution of calcium lignosulfonate, then freeze-drying it, and then crushing and sieving it to obtain the modified biomass carbon. Freeze-drying increases the adsorption amount of calcium lignosulfonate and the specific surface area of the modified biomass carbon, thereby improving the contact with powders such as cement and improving the impermeability.
[0027] Furthermore, the mass fraction of calcium lignosulfonate in the calcium lignosulfonate aqueous solution is 5-12%, and the mass ratio of the carbonized biomass to calcium lignosulfonate is (5-10):1.
[0028] Furthermore, the carbonization treatment time is 1-3 hours; the crushing and screening refers to passing through a 100-200 mesh sieve.
[0029] Furthermore, the biomass includes one or more of straw, rice husk, hemp stalk, wood chips, bark, bamboo chips and bamboo powder, branches, coconut shells, walnut shells, palm shells, peanut shells, and coffee grounds. Preferably, the biomass is rice husk, which contains a certain amount of silicon dioxide, which helps to improve the strength of concrete and improves the anti-seepage effect through a slow release process.
[0030] Furthermore, the preparation method of the modified biomass carbon further comprises: mixing the freeze-dried product with a silane coupling agent, and then drying, crushing and sieving to obtain the modified biomass carbon. The silane coupling agent is used to improve the hydrophobicity of the modified biomass carbon, thereby improving the anti-seepage effect.
[0031] The silane coupling agent is KH550, hexadecyltrimethoxysilane, etc.
[0032] Furthermore, the fineness modulus of the sand is 2.3-3.3, and the crushed stone is 5-25 mm grade crushed stone.
[0033] like Figure 1 The present invention also provides a process for preparing a high performance concrete shield segment as described in any one of the above, comprising the following steps:
[0034] S1. Concrete preparation: preparing concrete according to the raw material ratio of the impermeable concrete;
[0035] S2. Fabrication and installation of steel cage: prepare the segment mold, apply the release agent, process the segment steel cage, and hoist it into the mold for positioning and installation;
[0036] S4, concrete pouring and vibrating: pouring the concrete obtained in step S1 into a mold, vibrating, and forming a casting body;
[0037] S5, curing and demoulding: curing the cast body to obtain shield segments.
[0038] Furthermore, the curing refers to first steam curing or natural curing until the compressive strength of the concrete reaches 20MPa, and then hoisting it to a water curing tank for curing for 7-28 days.
[0039] Example 1
[0040] A high-performance concrete shield segment comprises impermeable concrete and a steel cage. The impermeable concrete comprises, by mass, 300 parts of cement, 550 parts of crushed stone, 420 parts of sand, 36 parts of fly ash, 28 parts of steel fiber, 12 parts of modified biomass carbon, 6 parts of water reducing agent calcium wood sulfonate, and 80 parts of water.
[0041] The preparation method of modified biomass carbon includes: carbonizing rice husk at 550°C in an air atmosphere, then crushing it through a 100-mesh sieve to obtain biomass carbon; then adding it to an 8wt% calcium lignosulfonate aqueous solution and mixing it evenly, wherein the mass ratio of biomass carbon to calcium lignosulfonate is 6:1, then freeze-drying it at -40°C for 36 hours, and then crushing it through a 100-mesh sieve to obtain the modified biomass carbon.
[0042] The length of the steel fiber is 50mm and the diameter is 0.75mm. Reinforcement of the steel cage: inner reinforcement External reinforcement Auxiliary reinforcement includes frame reinforcement, reinforcing reinforcement, spiral reinforcement and waist reinforcement. The shield segment size is: inner diameter 8000mm, outer diameter 8800mm, ring width 1800mm.
[0043] The preparation process of high performance concrete shield segments includes the following steps:
[0044] S1. Concrete preparation: Mix the raw materials of the anti-seepage concrete according to the ratio to make concrete;
[0045] S2. Fabrication and installation of steel cage: prepare the segment mold, apply the release agent, process the segment steel cage, and hoist it into the mold for positioning and installation;
[0046] S4, concrete pouring and vibrating: pouring the concrete obtained in step S1 into a mold, vibrating, and forming a casting body;
[0047] S5. Curing and demoulding: The cast body is naturally cured until the concrete compressive strength reaches 20 MPa, and then hoisted to a water curing tank for curing for 28 days to obtain a shield segment.
[0048] Example 2
[0049] The difference from Example 1 is that the mass concentration of the calcium lignosulfonate aqueous solution is 5 wt %. The rest is the same as Example 1 and will not be described again.
[0050] Example 3
[0051] The difference from Example 1 is that the mass concentration of the calcium lignosulfonate aqueous solution is 12 wt %. The rest is the same as Example 1 and will not be described again.
[0052] Example 4
[0053] The difference from Example 1 is that the mass ratio of biomass carbon to calcium lignosulfonate is 10:1, and the rest is the same as Example 1 and will not be repeated here.
[0054] Example 5
[0055] The difference from Example 1 is that the preparation method of modified biomass carbon includes: carbonizing rice husk at 550°C in an air atmosphere, then crushing through a 100-mesh sieve to obtain biomass carbon; then adding to an 8wt% calcium wood sulfonate aqueous solution and mixing evenly, the mass ratio of biomass carbon to calcium wood sulfonate is 6:1, soaking for 1 hour, separating the solid and liquid, and drying, and then crushing through a 100-mesh sieve to obtain the modified biomass carbon. The rest is the same as Example 1 and will not be repeated here.
[0056] Example 6
[0057] The difference from Example 1 is that the rice husk is replaced by coconut husk. The rest is the same as Example 1 and will not be repeated here.
[0058] Comparative Example 1
[0059] The difference from Example 1 is that a high-performance concrete shield segment includes impermeable concrete and a steel cage, and the impermeable concrete includes, by mass, 300 parts of cement, 550 parts of crushed stone, 420 parts of sand, 36 parts of fly ash, 28 parts of steel fiber, 6 parts of water reducer, and 80 parts of water. The rest is the same as Example 1 and will not be repeated here.
[0060] Comparative Example 2
[0061] The difference from Example 1 is that the preparation method of modified biomass carbon includes: carbonizing rice husk at 550° C. in air atmosphere, and then crushing through a 100-mesh sieve to obtain biomass carbon. The rest is the same as Example 1 and will not be repeated here.
[0062] The shield segments were tested for impermeability in accordance with GB / T 22082 "Precast Concrete Lining Segments". The compressive strength of the impermeable concrete (i.e., the concrete pipe obtained by direct curing by removing the steel cage according to S1 and S5) was tested in accordance with GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete".
[0063] Table 1 Performance test results of embodiments and comparative examples
[0064] Sample 28d compressive strength (MPa) Maximum water pressure (MPa) Maximum water pressure penetration depth (mm) Example 1 58.9 2.6 30.6 Example 2 56.7 2.6 35.2 Example 3 58.6 2.6 32.1 Example 4 55.3 2.2 30.2 Example 5 56.1 2.6 36.8 Example 6 57.5 2.2 28.9 Comparative Example 1 54.4 2.0 55.8 Comparative Example 2 54.8 2.0 50.6
[0065] As can be seen from Table 1, when the mass concentration of the calcium lignosulfonate aqueous solution changes, the compressive strength and water seepage depth change, but since the mass ratio of biomass carbon and calcium lignosulfonate remains unchanged. Therefore, the strength and water seepage depth are not greatly affected. When the mass ratio increases, that is, the amount of calcium lignosulfonate used decreases, the compressive strength decreases and the maximum anti-seepage pressure decreases. When solid-liquid separation and drying are used, the calcium lignosulfonate loading is reduced, and the specific surface area is reduced, so the compressive strength is also reduced, and the water seepage depth increases. When coconut shells are used, due to the reduction in silica content, the strength is also reduced, and the maximum anti-seepage pressure is reduced. When no modified biomass is added, the compressive strength and the maximum anti-seepage pressure are both reduced, indicating that the anti-seepage performance is deteriorated. When the modified biomass does not adsorb calcium lignosulfonate, the anti-seepage performance is also reduced, indicating that the present invention can improve the anti-seepage performance by loading and slowly releasing calcium lignosulfonate.
[0066] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high performance concrete shield segment, characterized in that: The invention comprises impermeable concrete and a steel cage. The impermeable concrete comprises, by weight, 280-330 parts of cement, 500-570 parts of crushed stone, 400-480 parts of sand, 30-45 parts of fly ash, 20-35 parts of steel fiber, 5-18 parts of modified biomass carbon, 5-8 parts of water reducing agent and 70-90 parts of water. The modified biomass carbon is obtained by carbonizing biomass with a crude fiber content of ≥30% and then adsorbing calcium wood sulfonate.
2. The high performance concrete shield segment according to claim 1, characterized in that: The preparation method of the modified biomass carbon comprises: carbonizing the biomass at 500-700°C, then crushing and sieving; then adding the biomass into a calcium lignosulfonate aqueous solution, then freeze-drying, and then crushing and sieving to obtain the modified biomass carbon.
3. The high performance concrete shield segment according to claim 2, characterized in that: The mass fraction of calcium lignosulfonate in the calcium lignosulfonate aqueous solution is 5-12%.
4. The high performance concrete shield segment according to claim 2, characterized in that: The mass ratio of carbonized biomass to calcium lignosulfonate is (5-10):
1.
5. The high performance concrete shield segment according to claim 2, characterized in that: The carbonization treatment time is 1-3 hours; the crushing and screening refers to passing through a 100-200 mesh sieve.
6. The high performance concrete shield segment according to claim 2, characterized in that: The biomass includes one or more of straw, rice husk, hemp stalk, wood chips, bark, bamboo chips and bamboo powder, branches, coconut shells, walnut shells, palm shells, peanut shells, and coffee grounds.
7. The high performance concrete shield segment according to claim 2, characterized in that: The preparation method of the modified biomass carbon further comprises: mixing the freeze-dried product with a silane coupling agent, and then drying, crushing and sieving to obtain the modified biomass carbon.
8. The high performance concrete shield segment according to claim 1, characterized in that: The fineness modulus of the sand is 2.3-3.3, and the crushed stone is 5-25 mm grade crushed stone.
9. A process for preparing a high performance concrete shield segment according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Concrete preparation: preparing concrete according to the raw material ratio of the impermeable concrete; S2. Fabrication and installation of steel cage: prepare the segment mold, apply the release agent, process the segment steel cage, and hoist it into the mold for positioning and installation; S4, concrete pouring and vibrating: pouring the concrete obtained in step S1 into a mold, vibrating, and forming a casting body; S5, curing and demoulding: curing the cast body to obtain shield segments.
10. The preparation process according to claim 9, characterized in that: The curing refers to steam curing or natural curing until the compressive strength of the concrete reaches 20MPa, and then hoisting it to a water curing tank for curing for 7-28 days.
Citation Information
Patent Citations
Anti-crack concrete for shield segment and preparation method of anti-crack concrete
CN114988813A
Air-added brick produced by modified straw ash and method for processing air-added brick
CN102887674A
Aerated brick produced by using palygorskite and processing method of aerated brick
CN102887722A
High-strength impermeable anti-freezing concrete and preparation method thereof
CN111003981A
Anti-erosion concrete and preparation method thereof
CN115974490A